Pengaruh Financial Attitude dan Self Control Terhadap Financial Management Behavior dalam Penggunaan Layanan Pay Later: Studi Pengguna Kredivo di Kota Surabaya - Puspa Dwi Liestiyanti; Sonja Andarini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Kredivo is one of the pay later service applications in Indonesia and one of the reasons people use pay later is because of its easy terms, but this will result in waste and debt accumulation which will affect credit reputation due to not being able to manage finances (financial management behavior). The purpose of this study is to anticipate the attitude of waste and accumulation of individual debt by analyzing the attitude of individuals in managing and deciding their finances (financial attitude) and also seen from the ability of individuals to control themselves against spending (self control). This type of research uses associative and quantitative approaches. The sample used amounted to 160 respondents obtained through filling out a questionnaire using Google form with non probability sampling technique and purposive sampling method. The study used a data processing tool technique, namely IBM SPSS Statistics 26 with tests consisting of a Validity Test, Reliability Test, Classical Assumption Test (Normality Test, Multicollinearity Test, Heteroscedasticity Test), Multiple Linear Regression Test, and Hypothesis Test (F Test and t Test). The results showed that the financial attitude and self-control variables had a simultaneous (joint) effect on financial management behavior. Then the financial attitude variable and the self control variable partially (independently) affect financial management behavior.